Sensory functions and their relation to balance metrics: a secondary analysis of the LIMBIC-CENC multicenter cohort - van der Veen, Susanne M.; Perera, Robert; Fino, Peter C.; Franke, Laura Manning; Agyemang, Amma A.; Skop, Karen; Wilde, Elisabeth A.; Sponheim, Scot R.; Stamenkovic, Alexander; Thomas, James S.; Walker, William C. (Frontiers in Neurology, 2023)
Introduction Among patients with traumatic brain injury (TBI), balance problems often persist alongside hearing and vision impairments that lead to poorer outcomes of functional independence. As such, the ability to regain premorbid independent gait may be dictated by the level of sensory acuity or processing decrements that are shown following TBI assessment. This study explores the relationships between standardized sensory acuity and processing outcomes to postural balance and gait speed. Methods Secondary analysis was performed on the Long-Term Impact of Military- Relevant Brain Injury Consortium Chronic Effects of Neurotrauma Consortium LIMBIC (CENC) data set. Separate regression analyses were carried out for each of the balance assessments (via Computerized Dynamic Posturography, CDP) and walking speed. Discussion TBI frequency was significantly related to the majority of single CDP outcomes (i.e., Conditions 2–6), while various sensory processing outcomes had task-specific influences. Hearing impairments and auditory processing decrements presented with lower CDP scores (CDP Conditions 3,5,6, and 1–3 respectively), whereas greater visual processing scores were associated with better CDP scores for Conditions 2,5, and 6. In sum, patients with TBI had similar scores on static balance tests compared to non-TBI, but when the balance task got more difficult patients with TBI scored worse on the balance tests. Additionally, stronger associations with sensory processing than sensory acuity measures may indicate that patients with TBI have increased fall risk.